The future role of the use of sewage effluent for irrigation in the Near East - Arar A. (Reuse of low quality water for irrigation, 1989)
Increasing the conventional water supplies by non-conventional water development techniques has been applied in the Near East, and is gaining wider support. However, it has been limited in application and only recently plans have been formulated for large-scale development of this non-conventional source of supply. With the development of new technology and rising cost of water developed by conventional methods or by desalinisation, there is a new opportunity in the field of wastewater reuse. Sewage irrigation ensures the reuse of resources and achieves the best treatment of municipal wastewater. Efforts should be focused on maximising the benefits and on minimising any detrimental effects on people or the environment. A policy for wastewater reuse must be clearly established prior to any development activity in this field. An obvious basis for such a policy is to limit the use of treated effluent for purposes excluding potable uses, which would avoid or minimise the risk of human contact.
Aswan Seminar, 1988/01/16-21, Cairo (Egypt)